A systematic review of transcatheter aortic valve implantation via carotid artery access. (15th September 2016) - Stonier, Thomas; Harrison, Michael; Choong, Andrew M.T.L.
Abstract: Background: The carotid artery is a novel access route for transcatheter aortic valve implantation (TAVI). This may represent a viable alternative in patients unsuitable for TAVI via traditional transfemoral access, up to 20%, as well as other access routes such as subclavian, transapical and aortic. This systematic review summarises the current evidence for its safety and feasibility. Methods: A systematic review was conducted as per the Preferred Reporting Instructions for Systematic Reviews and Meta-analysis (PRISMA) guidelines using five electronic databases. Results: 16 studies were identified, including three prospective cohort studies, one retrospective cohort study, three case series and eight case reports. Data on 74 patients (mean age 76.9 years) was extracted including pre-operative work-up, technical procedure details and outcomes. This found 1 intraoperative death, 2 further deaths within 30 days, two incidences of transient ischaemic attack, no incidences of stroke, myocardial infarction, carotid access site complications or infection, 1 patient required new dialysis and 1 patient had an intraoperative dissection which resolved. Follow-up from 30 days to 1 year showed symptomatic improvement and echocardiographic improvement in line with those seen in transfemoral TAVI. Conclusions: The available data on TAVI via carotid access demonstrate technical feasibility with comparable outcomes to other traditional access routes. A low number of patients, heterogeneous clinical endpoints and relatively short follow-up periods limit formal meta-analysis and firmer conclusions. For patients in which other access routes are impossible, TAVI via carotid access represents a viable and potentially crucial alternative in patients who might otherwise be untreatable.